Identification of gene expression changes in transgenic C. elegans overexpressing human α-synuclein - Suvi Vartiainen; Petri Pehkonen; Merja Lakso; Richard Nass; Garry Wong (Neurobiology of Disease, 2006)
α-Synuclein containing cellular inclusions are a hallmark of Parkinson Disease, Lewy Body Dementia, and Multiple System Atrophy. A genome wide expression screen was performed in C. elegans overexpressing both wild-type and A53T human α-synuclein. 433 genes were up- and 67 genes down-regulated by statistical and fold change (> or <2) criteria. Gene ontology (GO) categories within the regulated gene lists indicated over-representation of development and reproduction, mitochondria, catalytic activity, and histone groups. Seven genes (pdr-1, ubc-7, pas-5, pas-7, pbs-4, RPT2, PSMD9) with function in the ubiquitin–proteasome system and 35 mitochondrial function genes were up-regulated. Nine genes that form histones H1, H2B, and H4 were down-regulated. These results demonstrate the effects of α-synuclein on proteasome and mitochondrial complex gene expression and provide further support for the role of these complexes in mediating neurotoxicity. The results also indicate an effect on nuclear protein genes that suggests a potential new avenue for investigation.